A simulation of risk management in information system projects for industrial engineering postgraduates - Sakgasit Ramingwong (2018)
© Int. J. of GEOMATE. Risks management is an essential element which can help increasing success rate in engineering projects. Undeniably, efficient implementation of this process requires not only knowledge but also real experience in the project context. In information system projects, which are widely known for its challenging and unique nature, the importance of risk management increase substantially. It is significant that all stakeholders, either at technical, management or other levels, need to realize the potentials of major risks. This research reports a result from an implementation of a simulation on risk management in information system projects based on a simulation called ARMI: A Risk Management Incorporation for industrial engineering postgraduate students. The results show that the simulation can be effectively implemented for participants with non-technical background.